1998
DOI: 10.3354/meps169065
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification of mercury in an Antarctic marine coastal food web

Abstract: ABSTRACT. Total 1lg concentrations were determined in marine sedlments and biota from the inner shelf of Terra Nova Bay (Antarctica). Like published data on air, snow and soils from the same region, Hg levels in the finest fraction of marine sediments were among the lowest ever reported for coastal marine environments (0.012 r 0.007 pg g-' dry wt). A progressive increase in Hg concentrations was found in organisms at different levels of the marine food web (phytoplankton < zooplankton and benthic primary consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
87
6
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(112 citation statements)
references
References 28 publications
16
87
6
3
Order By: Relevance
“…In spite of the lack of Hg measurements in the preys, this hypothesis was strongly supported by numerous literature data, which show that a progressive increase in Hg concentrations is usually found in organisms at different levels of the marine food web (e.g., Boudou and Ribeyre, 1997). For example Bargagli et al (1998) found systematically higher Hg concentration in polychaetes than in plankton in a study of an Antarctic marine ecosystem. Complementary studies on Hg content in prey invertebrates are thus needed to better apprehend the route of Hg accumulation in fishes from the Mediterranean and Black seas.…”
Section: Differences In Hg Concentration Between Red Mullets a Consementioning
confidence: 98%
“…In spite of the lack of Hg measurements in the preys, this hypothesis was strongly supported by numerous literature data, which show that a progressive increase in Hg concentrations is usually found in organisms at different levels of the marine food web (e.g., Boudou and Ribeyre, 1997). For example Bargagli et al (1998) found systematically higher Hg concentration in polychaetes than in plankton in a study of an Antarctic marine ecosystem. Complementary studies on Hg content in prey invertebrates are thus needed to better apprehend the route of Hg accumulation in fishes from the Mediterranean and Black seas.…”
Section: Differences In Hg Concentration Between Red Mullets a Consementioning
confidence: 98%
“…There are at least two approaches to examining the effects of trophic level: measuring metal levels in each link of the food chain leading to a top level predator (e.g. plankton, invertebrates, fish, fish-eating seabird; Hahn et al 1993;Bargagli et al 1998), and measuring levels in several members of the same group known to be in different trophic levels (e.g. seabirds at different trophic levels).…”
Section: Interspecific Comparisonsmentioning
confidence: 99%
“…Because some pollutants undergo biomagnification up the food chain, and can accumulate with age, concentrations are generally higher in top trophic level birds and mammals (Lewis and Furness, 1991;Ohlenhdorf, 1993;Bargagli et al, 1998;Scheifler et al, 2005). Factors that affect uptake, accumulation, and biomagnification of metals in birds include exposure pathways, species of the metal, and bioavailability, as well as a number of host factors, such as trophic status, location, foraging behavior, nutrition, body condition, gender, size, genetic variability, and age (Stewart et al, 1997;Debacker et al, 2001;Burger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%